Where are our heroes, martyrs and monuments? Archives of authors, publishers and editors from the Caribbean diaspora in London institutions. Issue 1 (November 2018) - Jenkins, Deborah
Abstract : This paper explores the collecting of Caribbean literary archives in London in the last five decades. It looks at the policies developed by community archives and by mainstream archive services active in the field in response to justified pressure from the Black community and from cultural agenda setters. Significant Black literary collections held in London are identified and described.